MANAJEMEN NYERI MENGGUNAKAN TERAPI MUSIK PADA PASIEN POST SECTIO CAESAREA: (STUDI KASUS DI RSUD PASAR REBO TAHUN 2013) - Irmawaty, Lenny; Ratilasari, Mekar (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2014)
Sectio caesarea is spending the fetus through an incision in the abdominal (laparotomy) and uterus wall (hysterectomy). During post operative periode, treatment process aimed to stabiling patient equilibrium and to eliminate the pain. Physiological reactions of the pain are autonomous nerve responds like speed of breathing, increase of the pulse and expenditure of adrenalin. Music can decrease of the pain because when the patient listen to the music, midbrain have produce beta endorphin hormone which can to eliminate pain neurotransmitter. The purpose in this research is music therapy on post Sectio caesarea surgery management pain at Pasar Rebo Hospital in 2013. Method: quasi experiment with pretest-posttest with control group, recruiting samples by purposive sampling, there were 42 respondents (21 respondents as the control group and 21 respondents as the intervention group). The pain was measured with Numeric Rating Scale (NRS). Statistic test used Paired Samples T-Test and Mann-Withney U. The result showed that: there was a significant effect of music therapy on post Sectio caesarea surgery management pain at Pasar Rebo Hospital in 2013. Music therapy is recommended for the independence nursing of maternity intervention to reduce post Sectio caesarea surgery pain.